Non-Compliance to Doctors Advices among Patients Suffering from Various Diseases: Patients Perspectives: A Neglected Issue - Memon, Khalida Naz; Shaikh, Nudrat Zeba; Soomro, Rafique Ahmed; Shaikh, Shazia Rehman; Khwaja, Anza Mansoor (Journal of Medicine, 2017)
Background: An acknowledgement of the patients perspectives about compliance towards doctors advices is critical in ensuring better results of medical consultation. The compliance to therapies is a primary determinant of treatment success.The authors found a serious dearth of research on this issue. Aim: The aim of the study was to determine the frequency & determinants of non-compliance towards doctors advices among study subjects. Method: The current community based descriptive cross sectional study was conducted on 230 subjects suffering from various illnesses. The patients were enrolled using convenience sampling. The data was collected on pre-structured Performa. The data comprises of questions regarding Patients compliance to doctor advises, that may be preventive, promotive and therapeutic care. Results: The mean age of respondents was 36.6 ± 7.4 years. The overall compliance to doctors advice was seen among 31.2% subjects. Compliance to treatment advice was 35.8 %; while towards health promotive advices was 29.5% & towards preventive advices against diseases was 28.4 percent.Seventy three percent of the total compliance was seento general practitionersin contrast to consultants i.e. 26.4%.Significant association was seen between compliance & older age (p=0.02), non-infectious diseases (p=0.04), severity of disease (p=0.01), oral route of administration (p=0.00) & shorter duration of disease (p=0.00). The results of association of compliance with gender however remained statistically insignificant. Conclusion: The study indicated that non-compliance towards doctors advices is a big public health issue & it should be taken as a hidden risk factor for diseases. The compliance towardsdoctorsadvice was more prevalent for non-communicable diseases compared to communicable diseases. Additionally, fear of side effects and high cost of medicine were two major reasons for treatment non-compliance. J MEDICINE January 2017; 18 (1) : 10-14